Best practices to support the self-determination of Indigenous communities, collectives, and organizations in health research through a provincial health research network environment in British Columbia, Canada - Erb, Tara; Stelkia, Krista (International Journal of Environmental Research and Public Health, 2023)
In Canada, the health research funding landscape limits the self-determination of Indigenous peoples in multiple ways, including institutional eligibility, priority setting, and institutional structures that deprioritize Indigenous knowledges. However, Indigenous-led research networks represent a promising approach to transforming the funding landscape to better support the self-determination of Indigenous peoples in health research. The British Columbia Network Environment for Indigenous Health Research (BC NEIHR) is one of nine Indigenous-led networks across Canada that supports research leadership among Indigenous (First Nations, Métis, and Inuit) communities, collectives, and organizations (ICCOs). In this paper, we share three best practices to support the self-determination of ICCOs in health research based on three years of operating the BC NEIHR: (1) creating capacity-bridging initiatives to overcome funding barriers; (2) building relational research relationships with ICCOs (“people on the ground”); and (3) establishing a network of partnerships and collaborations to support ICCO self-determination. Supporting the self-determination of ICCOs and enabling them to lead their own health research is a critical pathway toward transforming the way Indigenous health research is funded and conducted in Canada. The NEIHR program is generously funded by the Canadian Institute for Health Research (Canadian Institutes of Health Research: MN2-152406), and the BC NEIHR receives additional funding contributions from partners Michal Smith Health Research BC (MSHRBC), BC SUPPORT Unit, and the University of Victoria (UVic). Faculty Reviewed